Impact of the COVID-19 Pandemic on China's Stock Market Volatility, During and After the Outbreak: Evidence From an ARDL Approach - Jin, Cheng (Frontiers in Public Health, 2022)
Purpose : In this study, we empirically investigate the impact of the Covid-19 pandemic on China’s stock price volatility during and after its initial outbreak, using time-series daily data covering the period from July to October, 2020 and 2021 respectively. Design/methodology/approach : In the estimation, the ARDL bounds test approach was employed to examine the existence of co-integration and the relationship of long-run and short-run between the new infection rates and stock price volatility, as stable and unstable variables are mixed. The inner-day and inter-day volatility, based on the Shanghai (securities) composite index, are estimated in separate empirical models. In addition, the Inter-bank overnight lending rate (IBOLR) is controlled. Findings and implications : We find that in the initial year of the epidemic, the new infection rate is negatively correlated to stock prices in the short-term, whereas no significant evidence existed in the long-term. However, after the epidemic’s outbreak, the result depicts that new infections increased stock prices in the long-term, and depressed its inner-day volatility in the short-term, inconsistent with most investigations. This phenomenon may be due to the fact that investors were more concerned about the withdraw of stimulating policies, which were introduced to fight against the epidemic’s impact on economy, than the epidemic itself. This study complements the limitations of most existing studies which just focus on the period of the epidemic’s outbreak, and provides insight into macroeconomic policy making in the era of the post Covid-19 epidemic intervention in IBOLR and balance social & economic sustainability.